Kochia control with preemergence herbicides in soybeans, dose response of three Kochia populations to glyphosate, and response of corn, soybean, and grain sorghum to saflufenacil - Hulse, Brandon Michael (Kansas State University, 2012)
Kochia (Kochia scoparia (L.) Schrad) is a troublesome and highly competitive weed in many cropping systems in the Great Plains region. It has traditionally been controlled using postemergence (POST) applications of glyphosate, however control is becoming inconsistent. Use of preemergence (PRE) herbicides may help to control kochia. Objectives of this research were to (1) Evaluate the efficacy of selected PRE herbicides in combination with POST applied glyphosate for controlling kochia in soybeans, (2) evaluate a kochia population (Norton) response to various rates of glyphosate compared to previously characterized highly susceptible (Syracuse) and moderately resistant (Ingalls) kochia populations, and (3) quantify the effects of herbicide rate, planting depth, soil pH, and soil type on corn, soybean, and grain sorghum tolerance to saflufenacil. Field studies showed that glyphosate applied alone did not always provide adequate season-long kochia control. In general, PRE herbicide treatments provided effective kochia control. These data suggest that a sequential herbicide program with a PRE herbicide treatment followed by POST glyphosate will provide the most consistent kochia control in soybeans and help minimize the risk of developing herbicide resistant kochia. Greenhouse studies confirmed great variability in kochia susceptibility to glyphosate across three different kochia populations. In general, as glyphosate rates increased, kochia control increased with all three populations. At the field use rate of glyphosate, the Syracuse kochia population was controlled 94% 21 days after treatment (DAT), whereas the Ingalls and Norton populations were controlled 26 and 41% respectively. Nonlinear regression analysis for each population indicated the glyphosate rate required to cause 50% visible control (GR50) was 1.6, 1.1, and 0.31 times the field use rate of 870 g ae/ha for the Ingalls, Norton, and Syracuse kochia populations. Greenhouse studies indicated that soil type had the greatest impact on saflufenacil injury to corn, soybeans, and sorghum, with crop injury consistently being greater on a fine sandy loam soil with 0.9% organic matter than a silt loam soil with 3.9% organic matter. Soil pH, saflufenacil rate, and seed depth also may influence the risk of crop injury from saflufenacil, but were less important than soil type.
Keywords: Kochia; Saflufenacil; Agronomy (0285)